THEORETICAL BASIS OF THE PROCESS OF CONDENSATION PRODUCTS OF CHLORINATION AND THE FORMATION OF THE TITANIUM- AND CHLORO-CONTAINING WASTES WITH APPLICATION IN CONSTRUCTION - Savin, Yu. L. (Science and Transport Progress, 2008)
The studies of theoretical bases of condensation process of the products of the chlorination and formation of titaniumchlorine containing wastes with using them in construction industry are presented in the paper. The studies conducted have allowed creating the production technologies of silicate construction materials.